Clear Cell Carcinoma (CCC) of the Cervix Is a Human Papillomavirus (HPV)-independent Tumor Associated With Poor Outcome: A Comprehensive Analysis of 58 Cases. (5th June 2022) - Stolnicu, Simona; Karpathiou, Georgia; Guerra, Esther; Mateoiu, Claudia; Reques, Armando; Garcia, Angel; Bart, Joost; Felix, Ana; Fani, Daniela; Gama, Joao; Hardisson, David; Bennett, Jennifer A.; et al.
Abstract : Cervical clear cell carcinoma (CCC) is a rare human papillomavirus–independent adenocarcinoma. While recent studies have focused on gastric-type endocervical adenocarcinoma (GTA), little is known about CCC. A total of 58 (CCCs) were collected from 14 international institutions and retrospectively analyzed using univariable and multivariable methods and compared with 36 gastric-type adenocarcinomas and 173 human papillomavirus–associated (HPVA) endocervical adenocarcinoma (ECA) regarding overall survival (OS) and recurrence-free survival (RFS). Most cases were FIGO stage I (72.4%), with Silva C pattern of invasion (77.6%), and the majority were treated with radical surgery (84.5%) and adjuvant therapy (55.2%). Lymphovascular invasion was present in 31%, while lymph node metastasis was seen in 24.1%; 10.3% were associated with abdominopelvic metastases at the time of diagnosis; 32.8% had recurrences, and 19% died of disease. We did not find statistically significant differences in OS and RFS between CCC and GTA at 5 and 10 years ( P =0.313 and 0.508, respectively), but there were significant differences in both OS and RFS between CCC and HPVA ECA ( P =0.003 and 0.032, respectively). Also, OS and RFS in stage I clear cell and GTA were similar ( P =0.632 and 0.692, respectively). Multivariate analysis showed that OS is influenced by the presence of recurrence ( P =0.009), while RFS is influenced by the FIGO stage ( P =0.025). Cervical CCC has poorer outcomes than HPVA ECA and similar outcomes to human papillomavirus–independent GTA. Oncologic treatment significantly influences RFS in univariate analysis but is not an independent prognostic factor in multivariate analysis suggesting that alternative therapies should be investigated.